ESP Students’ Perception toward the Utilization of Tik Tok Application for Improving English Skills - Eka Wulandari; Yuyun Putri Mandasari (Prologue: Journal on Language and Literature, 2023)
Students' 21st-century talents, including their English language skills, must be cultivated in this increasingly globalized period. According to previous studies, this application is one of the finest approaches for English education. It is also popular for facilitating successful English learning, however, research on the usage of Tik Tok in the context of ESP, notably in English for Midwifery courses, is still lacking. The purpose of this study was to determine students' perceptions of utilizing Tik Tok for English learning in the post-pandemic era. This study included 61 students from the Midwifery Department at Poltekkes Kemenkes Malang during the academic year of 2022/2023. To collect data, online questionnaires and written interviews were provided to the students. The findings revealed that the students had a favorable attitude toward using Tik Tok to learn English.  This study examined students' perspectives on Tik Tok in English language acquisition in the context of ESP, specifically English for Midwifery. It is also suggested that Tik Tok be used as a learning media because it has been shown to be useful in assisting students in getting the chunk of learning objectives that positively impact their English skills, particularly in the ESP environment.